Analisis Proses Produksi Pada Usaha Budidaya Jamur Tiram Di Simpang Layang Kabupaten Bener Meriah - MSM, Zainuddin; Tniro, Alwin (Biram Samtani Sains, 2025)
This study describes the production process in the Oyster Mushroom Cultivation Business in Simpang Layang, Bener Meriah Regency. Data analysis used in this study is descriptive analysis, where the purpose of this analysis is to describe systematically, factually and accurately the facts and relationships between the phenomena being investigated. The analysis was carried out after the data needed in this study was collected. The data obtained regarding the stages of the mushroom production process in Simpang Layang. The results of the study can be concluded that the oyster mushroom production process has 9 (nine) stages of the production process, while the selling price of oyster mushrooms is around 40,000 / kg. This oyster mushroom cultivation business has reached 5,000 to 10,000 baglogs for F0 and F1 seeds ordered from the Medan area, while for F3 baglogs are made by themselves